Tecemotide (L-BLP25) versus placebo after chemoradiotherapy for stage III non-small cell lung cancer (START): a randomized, double-blind, phase III trial - DeGregorio, Michael; Soe, Lin; Wolf, Michael (Journal of Thoracic Disease, 2014)
Incorporating an effective and tolerable immunotherapeutic as part of maintenance therapy for unresectable stage III non-small-cell lung cancer (NSCLC) is a potential method of improving overall treatment outcomes (1). Many investigators in the lung cancer community have the research goal of establishing a maintenance therapy that prolongs overall survival by stabilizing disease without significantly decreasing quality of life. Immunotherapy capable of inducing an immune response against a tumorspecific antigen is one such approach anticipated to achieve this goal. The recent publication by Butts et al. of the Stimulating Targeted Antigenic Response To NSCLC (START) trial showed that the primary endpoint of a significant difference in overall survival in the treatment group was not met; however, the predefined subgroup of patients receiving concurrent chemoradiotherapy followed by maintenance therapy with tecemotide, an antigenspecific immunotherapy, received a notable survival benefit (n=806; HR 0.78, 95% CI 0.64-0.95, P=0.016) (2).